Prime effects in metaphor comprehension: comparing congruent and opposite schematic primes - Khatin-Zadeh, Omid; Farsani, Danyal; Eskandari, Zahra; Li, Lin; Banaruee, Hassan (Frontiers in Psychology, 2024)
This study investigates the role of priming in the process of metaphor comprehension focusing on both literal and gesture-based primes under congruent and opposite conditions. We conducted a two-stage experiment to explore how different priming conditions influence the cognitive processing of metaphors. In stage 1, participants made sensibility judgments on a set of metaphors in congruent literal primes (Group 1), opposite literal primes (Group 2), and no-prime conditions, with Group 3 serving as a baseline. In stage 2, participants performed the same task under congruent gesture-prime (Group 4) and opposite gesture-prime conditions (Group 5), again with Group 3 as the baseline. Sensibility judgements and reaction times were analyzed and compared across all five conditions. Findings of stage 1 reveal that congruent literal primes facilitate process of metaphor comprehension, whereas opposite literal primes delay the process of understanding the subsequent metaphor. Similarly, results of stage 2 show that congruent gesture primes facilitate the process of understanding the subsequent metaphor, while opposite gesture primes delay it.These results align with theories of embodied metaphor comprehension, highlighting the varying influences of primes on metaphor comprehension.